How do we enhance undergraduate healthcare education in dementia? A review of the role of innovative approaches and development of the Time for Dementia Programme. (10th October 2016) - Banerjee, Sube; Farina, Nicolas; Daley, Stephanie; Grosvenor, Wendy; Hughes, Leila; Hebditch, Molly; Mackrell, Sophie; Nilforooshan, Ramin; Wyatt, Chris; de Vries, Kay; Haq, Inam; Wright, Juliet
Abstract : Objectives: Traditional healthcare education, delivered through a series of time‐limited clinical placements, often fails to deliver an understanding of the experiences of those with long‐term conditions, a growing issue for healthcare systems. Responses include longitudinal integrated clerkships and senior mentor programmes allowing students' longer placements, continuity of contact and opportunities to learn about chronic illness and patient experience. We review their development and delivery in dementia and present the Time for Dementia (TFD) Programme, a novel 2‐year interdisciplinary educational programme. Design: The study design involves a scoping review of enhanced placements in dementia for healthcare professionals in training including longitudinal integrated clerkships and senior mentor programmes and a case study of the development of TFD and its evaluation. Results: Eight enhanced programmes in dementia were identified and seven in the USA. None were compulsory and all lasted 12 months. All reported positive impact from case study designs but data quality was weak. Building on these, TFD was developed in partnership between the Alzheimer's Society, universities and NHS and made a core part of the curriculum for medical, nursing and paramedic students. Students visit a person with dementia and their family in pairs for 2 h every 3 months for 2 years. They follow a semi‐structured interaction guide focusing on experiences of illness and services and complete reflective appraisals. Conclusions: We need interprofessional undergraduate healthcare education that enables future healthcare professionals to be able to understand and manage the people with the long‐term conditions who current systems often fail. TFD is designed to help address this need. © 2016 The Authors. International Journal of Geriatric Psychiatry Published by John Wiley & Sons Ltd.